2021
DOI: 10.1007/s00213-021-05854-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of nucleus accumbens microRNA-181a and MeCP2 in incubation of heroin craving in male rats

Abstract: Rationale Epigenetic regulation has been implicated in the incubation of drug craving (the time-dependent increase in drug seeking after prolonged withdrawal from drug self-administration). There is little information available on the role of microRNAs in incubation of heroin craving. Objective This study aimed to investigate the roles and mechanisms of miR-181a and methyl CpG binding protein 2 (MeCP2) in the nucleus accumbens (NAc) in incubation of heroin seeking. Methods MiRNA sequencing was used to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“… 24 Animals exhibit craving for a substance by engaging in behavioral indicators that have previously been paired with administration of the substance (e.g., nose pokes and lever presses). 24 , 28 This behavior is also seen when animals are withdrawn from HP foods. When HP foods are removed from the diet, rats exhibit general signs of anhedonia and low overall motivational drive.…”
Section: Animal Models Of Hp Food Withdrawalmentioning
confidence: 94%
See 2 more Smart Citations
“… 24 Animals exhibit craving for a substance by engaging in behavioral indicators that have previously been paired with administration of the substance (e.g., nose pokes and lever presses). 24 , 28 This behavior is also seen when animals are withdrawn from HP foods. When HP foods are removed from the diet, rats exhibit general signs of anhedonia and low overall motivational drive.…”
Section: Animal Models Of Hp Food Withdrawalmentioning
confidence: 94%
“…[48][49][50] Like other addictive substances, animal models provide evidence that HP foods or ingredients in these foods (i.e., sugar or fat) can change the reward system in a manner that makes removal of these foods from the diet aversive due to the physical and affective symptoms that emerge. 51 Neural reward changes in response to HP food withdrawal are particularly salient for adolescent rodents due to T A B L E 2 Current animal model evidence for HP food withdrawal Animals express physical indicators of withdrawal during HP food withdrawal 22,23 Animals display affective indicators of withdrawal during HP food withdrawal 24,25 Animals show neural reward dysfunction during HP food withdrawal [22][23][24][25][26][27][28] Animals show increased CRF expression during HP food withdrawal 29 Animals show enhanced motivational drive/craving to consume HP food during HP food withdrawal 26,30,31 Animals show increased binge eating behavior during HP food withdrawal 28 higher cortical and subcortical concentrations of dopamine during this stage. 52 Importantly, animals only demonstrate withdrawal-like symptoms after exposure to HP food and not following consumption of less rewarding, more nutritious foods like standard chow.…”
Section: Animal Models Of Hp Food Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that miRNA signaling in the NAc can impact opioid self-administration behavior. Overexpression of miR-181 in the NAc of heroin SA rats decreased heroin seeking after 14D of forced abstinence [ 61 ]. Similarly, NAc miR-218 inhibited heroin-induced reinforcement in both conditioned placed preference and self-administration [ 55 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, long ncRNAs can be regulated by cocaine at least 24 hrs after the last injection ( Bu et al, 2012 ). Also, microRNAs are regulated by cocaine, heroin, and methamphetamine in the NAc ( Eipper-Mains et al, 2011 ; Su et al, 2019 ; Dash et al, 2020 ; Yang et al, 2020 ; Li et al, 2021 ; Xu et al, 2021 ) and the dorsal striatum ( Hollander et al, 2010 ; Im et al, 2010 ). Finally, small nucleolar RNAs (snoRNAs) are also regulated by cocaine and knockdown of MBII-52 attenuates cocaine CPP ( Chen et al, 2014 ).…”
Section: Limitations and Challenges In The Field Of Epigenetics And S...mentioning
confidence: 99%